Trends in the regional development of medium-sized municipalities with a population between 10 and 50 thousand in Eastern Bulgaria - Petrov, Kamen; Tsonkov, Nikolay (Edelweiss Applied Science and Technology, 2025)
This article is devoted to the medium-sized municipalities of Eastern Bulgaria, which play an important role in forming the backbone of the Bulgarian regional economy in the context of the ongoing processes of transformation, optimization, structuring, and integration of Bulgarian society into the European Union. Thus, the study shows the extent to which these municipalities can play a strategic role in the systematization of regional development, and hence the formatting of a new geo-economic model of the functioning of the Bulgarian socio-economic space. Relevant comparisons, assessments, and analyses are made of medium-sized municipalities, which have a role to play in supporting large municipalities while simultaneously playing a pulling role towards smaller municipalities. Recommendations are drawn for modeling a new socio-economic development of the national territory from a pan-European perspective.